Development and Application of Akad Rahn in Nash Perspective - Fikri Ainul Qolbi; Bima Wahyu Adi Nugraha; Nur Cholis Pratomo Wibowo; Muhammad Faisal Hamdi; Muhammad Syafiq Fajar Nugroho (Demak Universal Journal of Islam and Sharia, 2024)
An increasingly complex financial system requires Muslim scholars to closely observe the limits of what Sharia allows. The scholars of Fiqh agreed that Ar-Rahn could be done on the way and in a state of presence on the spot. As long as the collateral can be directly held/legally controlled by the receivable. This study used a descriptive qualitative method. In this case, the Rahn contract is analyzed using regulations, as well as the postulates underlying the formation of the contract to develop to this day. Financing accompanied by al-Rahn (al-Tamwil al-Mautsuq bi al-Rahn) is the permissibility of Rahn contracts only for accounts receivable (al-dain) which include factors of (1) qard contracts, (2) non-cash buying and selling (al-bai) and (3) lease contracts (ijarah) whose ujrah payments are non-cash or tajil.